Identification of amino acids in antigen-binding site of class II HLA proteins independently associated with hepatitis B vaccine response. Issue 4 (23rd January 2017) - Sakai, Aiko; Noguchi, Emiko; Fukushima, Takashi; Tagawa, Manabu; Iwabuchi, Atsushi; Kita, Masaki; Kakisaka, Keisuke; Miyasaka, Akio; Takikawa, Yasuhiro; Sumazaki, Ryo
Highlights: Case-control association study of HBV vaccine response in 574 university students. Conditional analyses identified responsible variants despite broad linkage disequilibrium in HLA. Amino acid variants in HLA-DRβ1 and -DPβ1 were independently associated with response. These variants located in antigen-binding pockets and regulated their physical properties. HBsAg presentation through HLA pocket structures will involve heterogeneity in vaccine response. Abstract: Background & aims: Genetic factors in class II human leukocyte antigen ( HLA ) have been reported to be associated with inter-individual variation in hepatitis B virus (HBV) vaccine response. However, the mechanism underlying the associations remains elusive. In particular, the broad linkage disequilibrium in HLA region complicates the localization of the independent effects of genetic variants. Thus, the present study aimed to identify the most probable causal variations in class II HLA loci involved in the immune response to HBV vaccine. Methods: We performed a case-control study to assess whether HLA-DRB1, - DQB1, and -DPB1 4-digit alleles were associated with the response to primary HBV vaccination in 574 healthy Japanese students. To identify causative variants, we next assessed independently associated amino acid variants in these loci using conditional logistic regression analysis. Furthermore, to clarify the functional effects of these variants on HLA proteins, we performed computational structural studies. Results: HLA-DRB1 ∗ 01:01, HLA-DRB1 ∗ 08:03, HLA-DQB1 ∗ 05:01, and HLA-DPB1 ∗ 04:02 were significantly associated with sufficient response, whereas HLA-DPB1 ∗ 05:01 was associated with poor response. We then identified amino acids independently associated with sufficient response, namely, leucine at position 26 of HLA-DRβ1 and glycine-glycine-proline-methionine at positions 84–87 of HLA-DPβ1. These amino acids were located in antigen-binding pocket 4 of HLA-DR and pocket 1 of HLA-DP, respectively, which are important structures for selective binding of antigenic peptides. In addition, the detected variations in HLA-DP protein were responsible for the differences in the electrostatic potentials of the pocket, which can explain in part the sufficient/poor vaccine responses. Conclusion: HLA-DRβ1 position 26 and HLA-DPβ1 positions 84–87 are independently associated with anti-HBs production against HBV vaccine. Our results suggest that HBsAg presentation through these HLA pocket structures plays an important role in the inter-individual variability of HBV vaccination.